Effect of biomass fuel use and kitchen location on maternal report of birth size: Cross-sectional analysis of 2016 Ethiopian Demographic Health Survey data - Girum Gebremeskel Kanno (Elsevier, 2021)
Objectives: Household air pollution from the use of biomass fuels has been associated with low birth weight in many developing countries. This study aimed to investigate the effect of indoor air pollution from biomass fuels and kitchen location on maternal reports of child size at birth in Ethiopia. Study design: A cross-sectional study design based on the secondary data analysis was used. Methods: A secondary data analysis was conducted using data from the 2016 Ethiopian Demographic Health Survey. Birth weight from child health cards and/or mother's recall was the dependent dichotomous variable. Fuel type was classified as high-pollution fuels (i.e. wood, straw, animal dung, crop residues, kerosene, coal and charcoal) and low-pollution fuels (i.e. electricity, liquid petroleum gas, natural gas and biogas). Hierarchical logistic regression was used to assess the effect of fuel type on birth weight. Adjusted odds ratios (AORs) and their 95% confidence interval (CIs) were calculated. A p-value less than 0.05 was considered significant. Results: The prevalence of low birth weight was 17% and 26.2% among low- and high-polluting fuel users, respectively. Compared with low-polluting fuels, the use of high-polluting cooking fuels was associated with an increased likelihood of low birth weight (unadjusted crude odds ratio 1.7; 95% CI 1.3, 2.3). AOR remained at 1.7 (95% CI 1.26, 2.3) after controlling for child variables. AOR after controlling for both child and maternal factors was 1.5 (95% CI 1.1, 2.1). In the final model, the association became insignificant with an AOR of 1.3 (95% CI 0.9, 1.9). The kitchen location, gender of the baby, mother's anaemia status, maternal chat chewing and wealth index were significant factors in the final model. Conclusions: In this study, the use of biomass fuels and kitchen location were associated with reduced child size at birth. Further observational studies should investigate this association using more direct methods for measurement of exposure to smoke emitted from biomass fuels on birth weight.